2016
DOI: 10.1371/journal.pone.0156758
|View full text |Cite
|
Sign up to set email alerts
|

P120-Catenin Regulates Early Trafficking Stages of the N-Cadherin Precursor Complex

Abstract: It is well established that binding of p120 catenin to the cytoplasmic domain of surface cadherin prevents cadherin endocytosis and degradation, contributing to cell-cell adhesion. In the present work we show that p120 catenin bound to the N-cadherin precursor, contributes to its anterograde movement from the endoplasmic reticulum (ER) to the Golgi complex. In HeLa cells, depletion of p120 expression, or blocking its binding to N-cadherin, increased the accumulation of the precursor in the ER, while it decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Many in vitro studies have demonstrated the importance of the interactions between the catenin proteins and type I cadherins for normal cadherin function. P120-catenin and β-catenin have both been reported as required for the transport of Ncad and Ecad to intercellular adherens junctions where they functions in adhesion complexes (Chen et al, 2003, Wehrendt et al, 2016, Chen et al, 1999, Wahl et al, 2003). In support of the previous studies, our data showed that reducing levels of Ncad does not affect levels of β-catenin, but that increasing Ncad increases the membrane-associated β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro studies have demonstrated the importance of the interactions between the catenin proteins and type I cadherins for normal cadherin function. P120-catenin and β-catenin have both been reported as required for the transport of Ncad and Ecad to intercellular adherens junctions where they functions in adhesion complexes (Chen et al, 2003, Wehrendt et al, 2016, Chen et al, 1999, Wahl et al, 2003). In support of the previous studies, our data showed that reducing levels of Ncad does not affect levels of β-catenin, but that increasing Ncad increases the membrane-associated β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, direct interaction of E-cadherin with p120-catenin (encoded by CTNND1; hereafter denoted p120) is required for E-cadherin stability and retention on the cell surface. In many cell types, cadherin adhesion is compromised or lost altogether upon removal of p120, as the remaining components of the complex are then internalized by endocytosis and degraded (Thoreson et al, 2000;Ozawa, 2003;Wehrendt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…a previous study examined the role of cx43 in chronic pain (28); however, to the best of our knowledge, the relationship between p120 and chronic pain remains to be elucidated. p120 is known to exhibit a role in adhesion among cells and in signal transduction in cells (29)(30)(31)(32). it has also been reported that p120 protects against post-traumatic inflammation by regulating the adherens and tight gap junctions (33,34).…”
Section: Discussionmentioning
confidence: 99%